Green Infrastructure Finance : A Public-Private Partnership Approach to Climate Finance - Baietti, Aldo (World Bank, Washington, DC, 2013)
In June 2012, the Green Infrastructure Finance Framework Report was published to address the constraints in financing green infrastructure and to develop a new approach to accelerate investments in low-emission technologies. The approach includes a financing and advisory interface, which clarifies the principles and concepts of the shared financing roles recommended by the methodology. The Framework attempts to bring clean investments towards a more familiar financing environment and to distance them from the charged political debate that has adversely affected the progress in international climate change discussions for over a decade. The detrimental effect of climate change is growing, yet clean investments are still grossly insufficient making it necessary to rethink the approach to greening the global energy mix. The need for some level of concessional financing or outright subsidy support is widely understood but the approach must be equitable, non-political and deliver a sufficient level of support. The concept of anchoring regulation in a country's existing public-private partnership (PPP) framework to focus on creating the right policy environment will greatly facilitate mainstream implementation and reduce costs. This aspect of the framework is widely understood by many developing country governments and can be easily replicated not only in East Asia, but also in other regions.